Hydrodynamic evaluation of the influence of outlet configuration for mechanical flocculation facilities - Cestari, J. L. [UNESP]; Matsumoto, T. [UNESP]; Gebara, D. [UNESP]; Sobrinho, M. Dall'Aglio [UNESP]; Libanio, M. (Iwa Publishing, 2016)
This paper focuses on hydrodynamic research aiming at the short-circuit evaluation of five different outlet configurations through the compartments of a mechanical flocculation unit of vertical shaft with mixing paddles at pilot scale. The tests were carried out with two, three and four compartments, variable and constant velocity gradients, including alternating senses of paddle rotation (clockwise in the first compartment, anticlockwise in the following one and so on). The research pointed out that the relevance of outlet configuration increases with the reduction of the number of compartments. In opposite, the velocity gradient and the sense of the paddle rotation seem less significant features. These results suggest the possibility of a viable increasing of performance, with low financial investments, mainly for flocculation units with three or two compartments installed in overloaded water treatment plants.
Keywords: hydrodynamic evaluation; mechanical flocculation; model of series of stirred tanks; outlet configuration; short-circuit; water treatment